THE INFLUENCE OF OWNERSHIP STRUCTURE AND AUDIT COMMITTEE ON INCOME MANAGEMENT WITH INDEPENDENT BOARD OF COMMISSIONERS 'PROPORTION AS MODERATING VARIABLES IN INFRASTRUCTURE, UTILITY AND TRANSPORTATION COMPANIES REGISTERED ON THE IDX - Muhammad Salman; Nur Kintan Nia (Universitas Putera Batam, 2020)
The purpose of this study is to examine the effect of managerial ownership structure, institutional ownership structure and audit committee on earnings management with the proportion of independent board of commissioners as a moderating variable. The samples in this study are infrastructure, utility and transportation companies listed on the Indonesia Stock Exchange (BEI) 2009. -2018 6 companies were selected using purposive sampling method. The result of the multiple linear regression equation is Y = -0,827 + 0,007 X1 + 0,006 X2 + 0,121 X3 + 0,032 M + 0,006 X1.M + 0,011 X2.M - 0,675 X3.M. The results showed that ownership structure, institutional ownership structure, audit committee and the proportion of independent commissioners did not have a significant effect on partial earnings management. Based on the partially moderated regression analysis test, the proportion of independent board of commissioners cannot moderate the effect of managerial ownership structure on earnings management, the proportion of independent board of commissioners cannot moderate the effect of institutional ownership structure on earnings management, the proportion of independent board of commissioners cannot moderate the effect of the audit committee on earnings management and simultaneously the proportion of independent board of commissioners can moderate the influence of managerial ownership structure, institutional ownership structure and audit committee on earnings management.